An unusual adenine phosphoribosyltransferase pseudogene is syntenic with its functional gene and is flanked by highly polymorphic DNAs. - Dush, M K (1986)
A mouse adenine phosphoribosyltransferase (aprt) pseudogene that had previously been recovered from a BALB/c sperm DNA library possessed several unusual features. Its nucleotide sequence, like that of other processed pseudogenes, was colinear with its corresponding mRNA, but it was truncated at its 3' end and lacked a poly(A) tail. The pseudogene was 82% homologous with corresponding regions of the functional gene and had incurred mutations that included transitions, transversions, deletions, and a point insertion. Even though the pseudogene was truncated within the protein-coding region of the corresponding functional gene, it was flanked at both ends by 13-base-pair direct repeats. Curiously, the direct repeats exhibited homology to APRT mRNA at the site of pseudogene divergence. The pseudogene appeared to be common to BALB/c and A/J mice, but it was contained on a 3-kilobase EcoRI fragment in the former strain and a 4.5-kilobase EcoRI fragment in the latter. The BALB/c and apparently the A/J pseudogene both mapped to chromosome 8, which also contains the functional aprt gene. The DNA sequences immediately surrounding the pseudogene in the two strains appeared to be similar, suggesting that the BALB/c and A/J pseudogenes are allelic. However, DNA sequences more distal to the pseudogene in the two strains appeared to vary. Thus, the EcoRI polymorphism was not due to simple loss of an EcoRI site, but was more complex. The pattern of flanking restriction sites was different for each of several enzymes, consistent with extensive DNA rearrangement. Double digests of BALB/c and A/J genomic DNAs revealed complex polymorphisms on both sides of the pseudogene. The results were consistent with insertion, deletion, or other rearrangement of DNA sequences that flank the pseudogene and suggest that this region of mouse chromosome 8 may be a region active for mutation or recombination.